The geopolitics of major power interventions in civil wars - Clare, Joe and Danilovic, Vesna (Political Research Quarterly)
What factors influence third parties to intervene in civil wars? Our focus on major powers, which are disproportionately more likely than other states to intervene in civil conflicts, directs us to the factors that uniquely shape their interests. While our study does not rule out humanitarian interventions by collective security international institutions and individual states, we do not find that humanitarian concerns motivate major powers. We argue and demonstrate that their decisions to intervene are principally motivated by their drive to establish, consolidate, or expand influence in different geopolitical regions. Past research with the strategic approach stressed the importance of an intervener$1 (Bs prior ties with a civil war state for this decision. Though important, we show the effect of these ties is subordinate to other factors. In our argument, their role is primarily relevant for determining whether an intervener will be on the side of the government or opposition. The key issue of whether major powers are likely to intervene in the first place, however, is contingent on how much the entire region is strategically relevant to warrant intervention. The empirical analysis of civil war interventions over nearly fifty years lends strong support to our theoretical expectations.- Reproduced s
Keywords: Civil war, Third-party interventions, Major powers, Geopolitics